A Molecular Tool Targeting the Base‐Flipping Activity of Human UHRF1. Issue 58 (13th September 2019) - Zaayter, Liliyana; Mori, Mattia; Ahmad, Tanveer; Ashraf, Waseem; Boudier, Christian; Kilin, Vasyl; Gavvala, Krishna; Richert, Ludovic; Eiler, Sylvia; Ruff, Marc; Botta, Maurizio; Bronner, Christian; et al.
Abstract: During DNA replication, ubiquitin‐like, containing PHD and RING fingers domains 1 (UHRF1) plays key roles in the inheritance of methylation patterns to daughter strands by recognizing through its SET and RING‐associated domain (SRA) the methylated CpGs and recruiting DNA methyltransferase 1 (DNMT1). Herein, our goal is to identify UHRF1 inhibitors targeting the 5′‐methylcytosine (5mC) binding pocket of the SRA domain to prevent the recognition and flipping of 5mC and determine the molecular and cellular consequences of this inhibition. For this, we used a multidisciplinary strategy combining virtual screening and molecular modeling with biophysical assays in solution and cells. We identified an anthraquinone compound able to bind to the 5mC binding pocket and inhibit the base‐flipping process in the low micromolar range. We also showed in cells that this hit impaired the UHRF1/DNMT1 interaction and decreased the overall methylation of DNA, highlighting the critical role of base flipping for DNMT1 recruitment and providing the first proof of concept of the druggability of the 5mC binding pocket. The selected anthraquinone appears thus as a key tool to investigate the role of UHRF1 in the inheritance of methylation patterns, as well as a starting point for hit‐to‐lead optimizations. Abstract : Base flipping inhibition : The anthraquinone compound UM63 binds to the 5‐methylcytosine (5mC) binding pocket of the SRA domain of UHRF1 and inhibits the base‐flipping process, which is crucial in the replication of DNA methylation profiles (see figure).